Identification and quantification of Cyanotoxins in Lake and household water around Lake Victoria, Kenya - Otoigo, Lilian (My University, 2020)
Cyanobacteria are single-celled algae that thrive in warm and nutrient rich water bodies. They can produce different kinds of toxins called cyanotoxins that can affect the liver. Cyanobacteria have been reported in Lake Victoria, which is an important source of drinking water for the riparian communities. This is as a result of eutrophication in Lake Victoria increasing the levels of cyanobacteria in the Nyanza Gulf. The purpose of this study was to identify and quantify microcystins in household and Lake Victoria water in Nyanza Gulf. In a longitudinal study adopting experimental design, six beaches were studied and 127 samples collected monthly from both households and beaches over six months. Cyanobacterial levels were determined using an enzyme assay method (PP2A) and microcystin strains identified using High Performance Liquid Chromatography (HPLC). Two-way ANOVA was done to determine statistical significance of microcystins. The results showed that all beaches were eutrophic resulting in flourishing of cyanobacteria. 84% of water samples contained microcystins. Concentration of microcystins was 3.44g/L. Microcystin RR (MC-RR) is the most abundant cyanotoxins followed by Microcystin YR (MC-YR) and Microcystin LR (MC-LR) is the least abundant in the Nyanza Gulf. There was significant variation between different beaches and different months (ANOVA: F=12.09, p<0.0005). This information provides an insight into the quality of Lake Victoria water for drinking based on quantities of microcystins in the sampled water. The study recommends regular monitoring of cyanobacterial cells in the lake water.
Keywords: Cyanobacteria; Cyanotoxins; Microcystins; PP2A; HPLC; Eutrophication